Open for Business : Building the New Cuban Economy - Feinberg, Richard E. (Book collections on Project MUSE., 2016)
An expert guide to Cuba's economic opening to the outside world. Ninety miles across the Straits of Florida, an exciting new revolution is afoot. This time, instead of guerillas marching down the streets of Havana, it is a global economy that will upend Cuba. Now opening to the world, what new forms is this nascent economy likely to take' Open for Business: The New Cuban Economy, Richard E. Feinberg's new book, examines the Cuban economy as it makes its early steps into developing a more dynamic market economy. He examines key issues like the role foreign investors will play, how Cubans will forge a path to entrepreneurship, and the roadmaps suggested by other emerging economies. As Cuba's economy awakens from the post-Castro dream, it will do so with a flavor that is uniquely Cuban. Feinberg's book-enriched by interviews and in-depth field research conducted over the last five years-speaks both to Cuba's legacy and to its new horizons on the world stage.